The Influence of Change Management, Leadership Style, Motivation, Work Conflict, and Work Stress on Employee Performance Workshop PT. Meratus Line Surabaya - Ashari B (Journal of Social Science and Business Studies, 2024)
This research aims to determine which change management, leadership style, motivation, work conflict and work stress have a dominant influence on employee performance. The research was conducted using a quantitative-descriptive approach. In this research, the population is all employees. The sampling technique in this research used a total sampling/census technique, namely, all employees totaling 74 respondents were the research sample. In this research, the data sources used include primary data and secondary data. Primary data was obtained directly from the main source of the research object by distributing questionnaires to relevant respondents. Meanwhile, secondary data was obtained from company documents or archives, as well as the results of interviews conducted. The analysis technique used in this research is multiple linear regression analysis. Based on the research results, it was found that change management variables, leadership style, motivation, work conflict and work stress simultaneously had a positive and significant effect on employee performance. Change management variables, leadership style, motivation, work conflict and work stress partially influence employee performance. Change management variables have a dominant influence on employee performance.